Molecular junctions by joining single-walled carbon nanotubes. - Terrones, M; Banhart, F; Grobert, N; Charlier, J; Terrones, H; Ajayan, P (2002)
Crossing single-walled carbon nanotubes can be joined by electron beam welding to form molecular junctions. Stable junctions of various geometries are created in situ in a transmission electron microscope. Electron beam exposure at high temperatures induces structural defects which promote the joining of tubes via cross-linking of dangling bonds. The observations are supported by molecular dynamics simulations which show that the creation of vacancies and interstitials induces the formation of junctions involving seven- or eight-membered carbon rings at the surface between the tubes.